Quantum-Safe Evaluation of TLS 1.3 Hybrid with ML-DSA - Jaya, Dery Yuswanto; Jakaria (Bahasa Indonesia, 2025)
Quantum computing poses a significant threat to classical cryptographic schemes widely used in modern networks, particularly RSA and ECC, which are vulnerable to Shor’s algorithm. To address this challenge, this study conducts a post-quantum security evaluation of TLS 1.3 by implementing hybrid X25519+Kyber key exchange and ML-DSA digital signatures. The objective is to assess the performance, overhead, and effectiveness of hybrid TLS in ensuring long-term data confidentiality within enterprise environments. The research method involves building a server–client testbed using OpenSSL with the oqs-provider, applying network load simulations under various latencies, and measuring key metrics including handshake latency, CPU utilization, certificate size, and client compatibility. The results indicate that hybrid TLS 1.3 with X25519+Kyber introduces only moderate handshake latency, while ML-DSA increases certificate size but remains manageable for deployment in modern enterprise systems. The conclusion of this study is that combining X25519+Kyber with ML-DSA offers an effective transition path towards quantum-safe networks without significantly sacrificing system performance..